Vertebrobasilar Contribution to Cerebral Arterial System of Dromedary Camels (Camelus dromedarius) - Al Aiyan, Ahmad; Menon, Preetha; AlDarwich, Adnan; Qablan, Moneeb; Hammoud, Maha; Shawaf, Turke; Richardson, Ken (Frontiers in Veterinary Science, 2021)
It is hypothesized that in the ‘more highly evolved’ mammals, including the domesticated mammals, that the brainstem and the cerebellum receive arterial blood through the vertebrobasilar system whilst the internal carotid arteries primarily supply the forebrain. In camels, the arterial blood supply to the brain differs from that of ruminants since the internal carotid artery and the rostral epidural rete mirabile (RERM) are both present and the basilar artery contributes a significant proportion of cerebral afferent blood. In this study, we described the anatomical distribution of the vertebrobasilar system arterial supply in the dromedary. Secondly, we determined the direction of blood flow within the vertebral and basilar arteries using transcranial color doppler ultrasonography. Thirdly, we quantified the percentage arterial contributions of the carotid and vertebrobasilar systems to the dromedary brain. Fifty-five heads of freshly slaughtered male Omani dromedaries aged 2 to 6 years were dissected to determine the distribution and topography of the arterial distribution to the brain. Their anatomical orientation was assessed by casting techniques using epoxy resin, polyurethane resin and latex neoprene. The epoxy resin and polyurethane resin casts of the head and neck arteries were used to measure the diameter of vertebrobasilar arterial system and carotid arterial system at pre-determined locations. These arterial diameters were used to calculate the percentage of blood supplied by each arterial system. The vertebrobasilar system in dromedary camels consists of paired vertebral arteries that contribute to the ventral spinal artery and basilar artery at multiple locations. In most specimens the vertebral artery was the primary contributor to the basilar artery compared to that of the ventral spinal artery. In four specimens the ventral spinal arteries appear to be the dominant contributor to the basilar artery. Transcranial color doppler ultrasonography confirmed that the direction of blood flow within the vertebral and basilar arteries was towards the brain in animals examined in ventral recumbency and when standing. The vertebrobasilar system contributes 34% of the blood supply to the brain. The vertebrobasilar system is the exclusive supply to the medulla oblongata, pons and cerebellum.